VP23R of Infectious Spleen and Kidney Necrosis Virus Mediates Formation of Virus-Mock Basement Membrane To Provide Attaching Sites for Lymphatic Endothelial Cells - Xu, Xiaopeng (American Society for Microbiology (ASM), 2010)
Putative open reading frames (ORFs) encoding laminin-like proteins are found in all members of the genus Megalocytivirus, family Iridoviridae. This is the first study that identified the VP23R protein encoded by ORF23R of the infectious spleen and kidney necrosis virus (ISKNV), a member of these genes of megalocytiviruses. The VP23R mRNA covering the ISKNV genomic coordinates 19547 to 22273 was transcribed ahead of the major capsid protein. Immunofluorescence analysis demonstrated that VP23R was expressed on the plasma membrane of the ISKNV-infected cells and could not be a viral envelope protein. Residues 292 to 576 of VP23R are homologous to the laminin γ1III2-6 fragment, which covers the nidogen-binding site. An immunoprecipitation assay showed that VP23R could interact with nidogen-1, and immunohistochemistry showed that nidogen-1 was localized on the outer membrane of the infected cells. Electron microscopy showed that a virus-mock basement membrane (VMBM) was formed on the surface of the infected cells and a layer of endothelial cells (ECs) was attached to the VMBM. The VMBM contained VP23R and nidogen-1 but not collagen IV. The attached ECs were identified as lymphatic endothelial cells (LECs), which have unique feature of overlapping intercellular junctions and can be stained by immunohistochemistry using an antibody against a specific lymphatic marker, Prox-1. Such infection signs have never been described in viruses. Elucidating the functions of LECs attached to the surface of the infected cells may be useful for studies on the pathogenic mechanisms of megalocytiviruses and may also be important for studies on lymphangiogenesis and basement membrane functions.